How Learning Interest, Motivation, and Outcome of Students in Learning Mathematics; The Comparative Study of the COVID-19 Pandemic and New Normal - Mawaddaturrohmah (Mathematics Research and Education Journal, 2022)
Interest, motivation, and learning outcomes always become the best variables in determining education success because these variables are the determiner factors in every element of education programs. This study compares interest, motivation, and learning outcomes between the COVID-19 pandemic and the new normal. This research is quantitative. The study population was all students at SMP Al-Ikhsan Boarding School, while the sample was two classes taken purposively. The research instrument was a structured observation sheet. The analytical technique used is descriptive statistics and independent-sample t-test. The analysis results show differences in motivation, interest, and student learning outcomes between the time of the pandemic and post-covid-19 pandemic with a significant 0.00.